Performance Optimisation of Proton Exchange Membrane Fuel Cell by Modifying Anode Flow Field Design - Vishnu Prasanna D; Parthiban D; Venkata Ramanan M; Rajesh D; Iyan Kumar R; Muninathan K (Advanced Energy Conversion Materials, 2024)
The study addresses the problem of optimizing the performance of proton exchange membrane (PEM) fuel cells, which are crucial for clean and efficient energy production. Traditional internal combustion (I.C.) engines are less efficient, with efficiencies below 35%, and contribute significantly to pollution. In contrast, PEM fuel cells have the potential for higher efficiencies and cleaner operation. This research is important as it seeks to enhance the efficiency of PEM fuel cells, thereby promoting sustainable energy solutions. The methods used in this study involved designing a 12 W capacity PEM fuel cell with both conventional and modified anode flow field designs. Performance optimization was carried out by comparing these designs under various operational conditions, measuring overall voltage efficiencies. The important results showed that the modified anode flow field design achieved an overall voltage efficiency of 45.52%, compared to 42.43% for the conventional design. This improvement of 7.2% in efficiency is significant and highlights the benefits of optimizing the anode flow field in PEM fuel cells. From these results, it can be concluded that modifying the anode flow field can lead to substantial improvements in fuel cell performance. The novelty of this work lies in its detailed experimental comparison and quantitative evidence of the enhanced performance of the modified anode flow field design, advancing previous efforts in the literature by providing clear and significant efficiency gains. This study goes beyond prior research by demonstrating a practical approach to increasing the efficiency of PEM fuel cells, which is essential for their broader application in clean energy technologies.